The Utility of the Repeatable Battery of Neuropsychological Status in Patients with Temporal and Non-temporal Lobe Epilepsy. (22nd November 2019) - Maiman, Moshe; Del Bene, Victor A; Farrell, Eileen; MacAllister, William S; Sheldon, Sloane; Rentería, Miguel Arce; Slugh, Mitchell; Gazzola, Deana M; Barr, William B
Abstract: Objective: The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) is a brief neuropsychological battery that has been validated in the assessment of dementia and other clinical populations. The current study examines the utility of the RBANS in patients with epilepsy. Methods: Ninety-eight patients with epilepsy completed the RBANS as part of a more comprehensive neuropsychological evaluation. Performance on the RBANS was evaluated for patients with a diagnosis of temporal lobe epilepsy (TLE; n  = 51) and other epilepsy patients (non-TLE, n  = 47) in comparison to published norms. Multivariate analysis of variance compared group performances on RBANS indices. Rates of impairment were also compared across groups using cutoff scores of ≤1.0 and ≤1.5 standard deviation s below the normative mean. Exploratory hierarchical regressions were used to examine the relations between epilepsy severity factors (i.e., age of onset, disease duration, and number of antiepileptic drugs [AEDs]) and RBANS performance. Results: TLE and non-TLE patients performed below the normative sample across all RBANS indices. Those with TLE performed worse than non-TLE patients on the Immediate and Delayed Memory indices and exhibited higher rates of general cognitive impairment. Number of AEDs was the only epilepsy severity factor that significantly predicted RBANS total performance, accounting for 14% of the variance. Conclusions: These findings suggest that the RBANS has utility in evaluating cognition in patients with epilepsy and can differentiate TLE and non-TLE patients. Additionally, number of AEDs appears to be associated with global cognitive performance in adults with epilepsy.